Serotonin Mediates Depression of Aggression After Acute and Chronic Social Defeat Stress in a Model Insect - Rillich, Jan; Stevenson, Paul A. (Frontiers in Behavioral Neuroscience, 2018)
In all animals, losers of a conflict against a conspecific exhibit suppressed aggressiveness, often coupled with depression-like symptoms, particularly after multiple defeats. While serotonin (5HT) is involved, discovering its natural role in aggression and depression has proven elusive. We show how 5HT influences aggression in male crickets, before, and after single and multiple defeats using serotonergic drugs, at dosages that had no obvious deleterious effect on general motility: the synthesis inhibitor alpha-methyltryptophan (AMTP), the receptor blockers ketanserin and methiothepin, the precursor 5-hydroxytryptophan (5HTP) and re-uptake inhibitor fluoxetine. Contrasting reports for other invertebrates, none of the drugs influenced aggression at the first encounter. However, crickets that received AMTP or ketanserin regained their aggressiveness sooner after defeat. In contrast, methiothepin and 5HTP dampened recovery, while fluoxetine prohibited it. Furthermore, compared to controls, which show long term aggressive depression after multiple defeat, those that received AMTP or ketanserin were significantly more resilient to chronic defeat stress. In contrast, 5HTP and fluoxetine increased susceptibility to defeat stress. We conclude that 5HT acts via a 5HT2 like receptor to maintain submissiveness after defeat, and promote the susceptibility to and establishment of long-term depression after chronic social defeat. Other data indicate that 5HT requires prior release of nitric oxide, and that it’s action could be mediated by inhibiting dopaminergic signalling. Similarities and differences to findings in mammals and other invertebrate model systems are discussed.